Entry of Borrelia burgdorferi into macrophages is end-on and leads to degradation in lysosomes. - Montgomery, R R (1996)
The Lyme disease spirochete, Borrelia burgdorferi, is ingested rapidly by mouse macrophages in vitro. Spirochetes attach by their ends and become progressively coiled as they move deeper into cells. From the earliest measurements, spirochetes colocalize with a marker of endosomes and lysosomes, and degradation of spirochetes occurs within lysosomes.